Membangun Percaya Diri Remaja Kristen melalui Mentoring Di Era Digital - Pekerti Mendrofa, Windy; Santosa; Tabrani, Ahmad (Institut Agama Kristen Negeri Manado, 2024)
Self-confidence plays a significant role and has influence in the lives of Christian teenagers in the digital era. Teenage confidence can be developed through non-formal Christian education. Mentoring is a strategy applied in non-formal Christian education. This research aims to describe the influence of mentoring implementation on the confidence of teenage participants in the non-formal Christian education program